Contextual Jihad And Mainstream Muslim Identity In Indonesia: The Case Of Republika Online - Rahman, Taufiqur (2015)
Jihad in the history of Islam has developed into a contested doctrine over a period of time. The term jihad as related to any exertion of power has been used by Muslim leaders to justify wars. On the other hand, the non-violent interpretation of jihad has been promoted by so-called moderate Muslim groups to support a moderating attitude towards colonial powers, un-Islamic authorities and non-Muslims in general. This paper investigates the discourse of jihad presented by Republika Online as the biggest Islamic commercial online news service in Indonesia. The paper argues that the description of jihad in Republika Online represents the contextual interpretation of jihad which is commonly held by the mainstream moderate Muslim groups in Indonesia. The description of contextual jihad can be seen as a process of negotiation between national identity and Islamic identity in Indonesia. This contextual interpretation suggests the possibility of the interpretation of the doctrine of jihad as an armed struggle as well as other generalised struggles depending on specific local conditions. This contextual interpretation also represents the construction of an integrated identity formation by projecting a distinct Indonesian Muslim identity which is Islamic in nature but also bounded by the awareness of a nationalist and an anti-imperialist identity